2014
DOI: 10.4103/0973-1296.127348
|View full text |Cite
|
Sign up to set email alerts
|

Antiasthmatic effects of schizandrae fructus extract in mice with asthma

Abstract: Background:Schizandrae fructus (SF), the fruit of Schisandra chinensis, has been used for the treatment of cough, wheezing, dry mouth, hepatitis, cardiovascular disease, and as a tonic and astringent in China, Japan, and Korea.Objective:Investigation of the antiasthmatic effects of SF.Materials and Methods:We investigated the effects of SF on airway hyperresponsiveness (AHR) to methacholine, production levels of antigen-specific antibodies, and histopathological changes in the lung tissue in a mouse model (Bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The results also suggest that the fruit extracts could be used as a complementary or alternative medicine to glucocorticoids (Kim et al 2014a). …”
Section: Current Knowledge Of Bioactivities and Pharmacological Applimentioning
confidence: 95%
“…The results also suggest that the fruit extracts could be used as a complementary or alternative medicine to glucocorticoids (Kim et al 2014a). …”
Section: Current Knowledge Of Bioactivities and Pharmacological Applimentioning
confidence: 95%
“…Nine major bioactive ingredients within S. chinensis were identified, including schisandrol A, schisandrol B, angeloylgomisin H, gomisin G, schisantherin A, schisanhenol, schisandrin A, schisandrin B, and schisandrin C16. Current reports demonstrated that these ingredients of S. chinensis possess several biological activities, such as antioxidant, antitumor, anti-inflammatory, and immunoregulatory activities15181920212223, and schisandrin A and schisandrin B exhibit antiviral activity against HIV24. Here, we investigated whether schisandrin A, schisandrin B, or schisandrin C could exhibit anti-DENV activity in vitro and in vivo and further investigated the molecular mechanism by which the effective ingredient inhibits DENV replication.…”
mentioning
confidence: 99%
“…Deoxyschizandrin has been shown to be associated with a variety of diseases such as chronic cough,[18] hepatoprotective,[19] and cardiovascular disease. [20] It has also been reported that deoxyschizandrin have diverse effects, such as anti-proliferative effects on tumor cells and pretreatment on physical exercise-induced muscle damage.…”
Section: Discussionmentioning
confidence: 99%